Evaluation of the Thermo Scientific™ SureTect™ Listeria monocytogenes Assay. (27th November 2019) - Cloke, Jonathan; Leon-Velarde, Carlos; Larson, Nathan; Dave, Keron; Evans, Katharine; Crabtree, David; Hughes, Annette; Hopper, Craig; Simpson, Helen; Withey, Sophie; Oleksiuk, Milena; Holopainen, Jani; et al.
Abstract: The Thermo Scientific™ SureTect™Listeria monocytogenes Assay is a new real-time PCR assay for the detection of Listeria monocytogenes in food and environmental samples. This assay was validated using the AOAC Research Institute (AOAC-RI) Performance Tested Methods SM program in comparison to the reference method detailed in International Organization for Standardization 11290-1:1996, including Amendment 1:2004 with the following foods and food contact surfaces: smoked salmon, processed cheese, fresh bagged spinach, fresh cantaloupe, cooked prawns (chilled product), cooked sliced turkey meat (chilled product), ice cream, pork frankfurters, salami, ground raw beef meat (12% fat), plastic, and stainless steel. All matrixes were tested by Thermo Fisher Scientific, Microbiology Division, Basingstoke, UK. In addition, three matrixes (pork frankfurters, bagged lettuce, and stainless steel) were analyzed independently as part of the AOAC-RI controlled laboratorystudy by the University of Guelph, Canada. Using probability of detection (POD) statistical analysis, a significant difference was demonstrated between the candidate and reference methods for salami, cooked sliced turkey and ice cream in favor of the SureTect assay. For all other matrixes, no significant difference by POD was seen between the two methods during the study. Inclusivity and exclusivity testing was also conducted with 53 and30 isolates, respectively, which demonstrated that the SureTect assay was able to detect all serotypes of L. monocytogenes . None of the exclusivity isolates analyzed were detectedby the SureTect assay. Ruggedness testing was conducted to evaluate the performance of the assay with specific method deviations outside the recommended parameters open to variation, i.e., enrichment time and temperature and lysis temperature, which demonstrated that the assay gave reliable performance. Accelerated stability testing was alsoconducted, validating the assay shelf life.